2012
DOI: 10.4172/2167-1052.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in HIV- infected Children on Antiretroviral Therapy at a Teaching Hospital in Lagos, Nigeria: A Retrospective Study

Abstract: Background: Highly active antiretroviral therapy (HAART) program requires adequate monitoring of the potential adverse events to the antiretroviral (ARV) drugs. We investigated the ARV drug combinations prescribed for HIV-infected children and their suspected adverse events.Methods: This is a retrospective and descriptive study involving HIV-infected children less than 15 years old who received treatment at the APIN clinic, Lagos University Teaching Hospital (LUTH) in Nigeria. The case files of 80 patients ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…The most common reasons being thrombocytopenia was, peripheral destruction of platelets due to crossreactivity of HIV antibodies, apoptosis of megakaryocytes due to direct HIV infection and abnormal and dysfunctional platelet production [54]. The prevalence was similar with a finding reported by Oshikoya et al [55] found to be 1.4%. However, this is lower than the prevalence 11.4% reported in DASH Lafia, Nigeria [48] and 11% in India [31].…”
Section: Plos Onesupporting
confidence: 85%
“…The most common reasons being thrombocytopenia was, peripheral destruction of platelets due to crossreactivity of HIV antibodies, apoptosis of megakaryocytes due to direct HIV infection and abnormal and dysfunctional platelet production [54]. The prevalence was similar with a finding reported by Oshikoya et al [55] found to be 1.4%. However, this is lower than the prevalence 11.4% reported in DASH Lafia, Nigeria [48] and 11% in India [31].…”
Section: Plos Onesupporting
confidence: 85%
“…Although rare AEs to pentazocine have not been reported in children, myofibrosis and its calcified form had been reported in adults following prolonged use of high-dose pentazocine [22,23]. Other rare AEs reported in adults include fibrosis at the injection site [24], irregular punched-out abscesses with a rim of hyper-pigmentation surrounding the ulcer [25,26], bilateral deep vein thrombosis, toxic epidermal necrolysis, generalized erythematous desquamative rash [27], fibromyositis and contracture [28].…”
Section: Introductionmentioning
confidence: 99%
“…: Types of surgery necessitating the use of pentazocine Note: * represents exploratory laparotomy with some specific procedures including wedge resection of the bowel and repair (28), manual reduction of intussusceptions only (26), bowel resection and anastomosis (15), excisional biopsy (7), hemicolectomy (6), appendectomy (4), bowel resection and loop colostomy (3), and manual reduction of intussusceptions with appendectomy (2).…”
mentioning
confidence: 99%